PERAN AUDIT INTERNAL TERHADAP KEPATUHAN PERANGKAT DAERAH DALAM PENGELOLAAN KEUANGAN PADA KANTOR INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA - Rambing, Thalia Amelia Constantie; Tinangon, Jantje J.; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Internal audit is an activity carried out independently, objectively believes in its examination, and conducts consultations in management with the aim of increasing the value and performance of the organization. The role of internal audit which is APIP (Government Internal Supervisory Apparatus) plays an important role in the government system, namely as a function of controlling where APIP is given responsibility in evaluating and evaluating and carrying out management functions, namely planning, organizing functions, directing function and coordinating function. The purpose of the study was to determine the role of internal audits on the compliance of regional devices in financial management and how APIP is independent in carrying out supervision and inspection. The method used in this study is a descriptive method that is by collecting data from the results of the study and then analyzing and drawing conclusions from the research. The results of the study obtained that the North Sulawesi Province Inspectorate was very instrumental in overseeing the financial management of regional equipment. This is evidenced by the implementation of its functions in the Internal Audit as the Government Internal Control Apparatus (APIP) which oversees and oversees the planning, organizing, directing and coordinating of financial management by SKPD in North Sulawesi.Keywords: Internal Audit, Role of Audit, Independent